Baseline characteristics of the omega‐3 fatty acids (Fish oils) and Aspirin in Vascular access OUtcomes in REnal Disease (FAVOURED) study. Issue 3 (March 2016) - Viecelli, Andrea K; Pascoe, Elaine M; Polkinghorne, Kevan R; Hawley, Carmel M; Paul‐Brent, Peta‐Anne; Badve, Sunil V; Cass, Alan; Johnson, David W; Kerr, Peter G; Mori, Trevor A; Scaria, Anish; Hooi, Seong L; et al.
Abstract: Aim: The Fish oils and Aspirin in Vascular access OUtcomes in REnal Disease (FAVOURED) trial investigated whether 3 months of omega‐3 polyunsaturated fatty acids, either alone or in combination with aspirin, will effectively reduce primary access failure of de novo arteriovenous fistulae. This report presents the baseline characteristics of all study participants, examines whether study protocol amendments successfully increased recruitment of a broader and more representative haemodialysis cohort, including patients already receiving aspirin, and contrasts Malaysian participants with those from Australia, New Zealand and the United Kingdom (UK). Method: This international, randomized, double‐blind, placebo‐controlled trial included patients older than 19 years with stage 4 or 5 chronic kidney disease currently receiving, or planned within 12 months to receive haemodialysis. Results: Participants ( n  = 568) were overweight (28.6 ± 7.3 kg/m 2 ), relatively young (54.8 ± 14.3 years), and predominantly male (63%) with a high prevalence of diabetes mellitus (46%) but low rate of ischaemic heart disease (8%). Sixty one percent were planned for lower arm arteriovenous fistula creation. Malaysian participants ( n  = 156) were younger (51.8 ± 13.6 years vs 57.1 ± 14.2 years, P  < 0.001) with a higher prevalence of diabetes mellitus (65% vs 43%, P  < 0.001), but less ischaemic heart disease (5% vs 14%, P  < 0.01) compared with the combined Australian, New Zealand and UK cohort ( n  = 228). Protocol modifications allowing for inclusion of patients receiving aspirin increased the prevalence of co‐morbidities compared with the original cohort. Conclusions: The FAVOURED study participants, while mostly similar to patients in contemporary national registry reports and comparable recent clinical trials, were on average younger and had less ischaemic heart disease. These differences were reduced as a consequence of including patients already receiving aspirin. Summary at a Glance: The Fish oils and Aspirin in Vascular access OUtcomes in REnal Disease (FAVOURED) trial investigated whether 3 months of omega‐3 polyunsaturated fatty acids, either alone or in combination with aspirin, would effectively reduce primary access failure of de novo arteriovenous fistulae. This report presents the baseline characteristics of all study participants, and examines whether study protocol amendments successfully increased recruitment of a broader and more representative haemodialysis cohort, including patients already receiving aspirin, and compares Malaysian participants with those from Australia, New Zealand and the United Kingdom. The FAVOURED study participants were on average younger and had less ischaemic heart disease than in contemporary national registry reports, and these differences were reduced as a consequence of including patients already receiving aspirin.